Tasmim Barnamij Mudaqqiq Sarfiy Li Tatwir Maharah al-Kitabah Lada al-Talabah al-Natiqin Bi Ghayr al-Arabiyyah Fi al-Jami'ah al-Islamiyyah al-'Alamiyyah Bi Maliziya Namujazan - Sahrir, Muhammad Sabri; Ahmed Mahmoud, Ahmad Ragheb (Penerbit UPSI, Perak Darul Ridzuan., 2021)
Tasmim Barnamij Mudaqqiq Sarfiy Li Tatwir Maharah al-Kitabah Lada al-Talabah al-Natiqin Bi Ghayr al-Arabiyyah Fi al-Jami'ah al-Islamiyyah al-'Alamiyyah Bi Maliziya Namujazan. Book Chapter in Published Book by UPSI.